DE VÍCTIMAS A INDIGNADOS: LA HISTORIA DEL MOVIMIENTO SOCIAL FAXINALENSE EN EL ESTADO DE PARANÁ - BRASIL - Campos, Roger Solis (2016)
This research analyzes the social movement known as the faxinalenses, who establish and make up traditional communities. These social groups are located in the State of Parana - Brazil and have a very particular life style based on the community. The main objective of the study is to analyze how social mobilization developed in the faxinais; It is argued on the assumption that there are new approaches, such as development as freedom from Amartya Sen (2000), where the concepts of development and freedom play important roles within human groups to facilitate participation in social and political decisions and encourage them to a dignified life and progress of the community. The latter can include the concept of dignity defined by Boaventura (2015) as the "good living, live well" that has generated new social movements since the Arab spring, known as the movement of “the indignants”. In this regard, research argues that the use of these concepts results in the creation of new perspectives on the future of faxinalenses’ social mobilization, contributing directly to their protection and conservation. Also, due to the characteristics of the object of study, qualitative methodology was used, as it is the most appropriate for analyzing social phenomena. On the other hand, to collect data the following techniques were used: the participant observation as 'complete observer', lifting secondary sources and interviews with faxinalenses. The data collected allowed the investigation to conclude that Faxinal communities have become victims of a system that is not compatible with the way they organize and live, which in turn has generated a wave of outrage among members of Faxinal. This outrage is justified because they do not feel protected by the state, as they have been affected by a disproportionate growth of the capitalist model, increasingly entering into their territory, diminishing and defacing their physical space and customs. Finally, do not have a development approach that suits your needs keeps relegated to live with dignity. It is important to emphasize that this research was supported by CAPES and the UNICENTRO Pro-Dean of Research.